The Photographer Photographed: A Conversation with Jean Mohr - Ross, Reuben Connolly (Imaginations)

(untitled) (York University, 2022)
The Swiss photographer Jean Mohr, who died in November 2018 at the age of 93, is well known for his long career documenting the plight of the displaced and dispossessed. Especially noteworthy are his collaborations with major intellectual figures, through which he experimented with the construction of visual narratives. His celebrated books with John Berger include *A Fortunate Man*, an intimate portrait of an English country doctor, and A Seventh Man, a meditation on migrant labour in 1970s Europe; with Edward Said, he published After the Last Sky, a reflection on Palestinian life through the fusion of text and photography. Partially based on a short interview conducted with Mohr in early 2018, this paper reflects on his life and work, taking the reader on a journey mediated by our conversation. In particular, I explore the development of his unique approach to photography and the experimental construction of visual narratives. In so doing, I argue that Mohr’s work offers social scientists, particularly those engaged in studying processes of migration or zones of conflict, ways of constructing more effective, more engaged, and more experiential accounts of complex social realities.